2020
DOI: 10.1080/14737175.2021.1836963
|View full text |Cite
|
Sign up to set email alerts
|

Acute ischemic stroke management: concepts and controversies.A narrative review

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research.-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 162 publications
0
23
0
Order By: Relevance
“…AF is the commonest cardiac rhythm abnormality observed in clinical practice and accounts for significant morbidity and mortality via the development of ischemic stroke ( 6 ), dementia ( 7 , 8 ) and heart failure ( 9 ). Shang et al reviewed the clinical applications and utility of AF characteristics, cardiac imaging and electrocardiogram markers, arterial stiffness and atherosclerosis-related markers, circulating biomarkers, and novel genetic markers for the diagnosis of ischaemic stroke and non-valvular AF.…”
Section: Risk Stratification For Cardiac Arrhythmiasmentioning
confidence: 99%
“…AF is the commonest cardiac rhythm abnormality observed in clinical practice and accounts for significant morbidity and mortality via the development of ischemic stroke ( 6 ), dementia ( 7 , 8 ) and heart failure ( 9 ). Shang et al reviewed the clinical applications and utility of AF characteristics, cardiac imaging and electrocardiogram markers, arterial stiffness and atherosclerosis-related markers, circulating biomarkers, and novel genetic markers for the diagnosis of ischaemic stroke and non-valvular AF.…”
Section: Risk Stratification For Cardiac Arrhythmiasmentioning
confidence: 99%
“… 4 , 5 Over the decades, great advances have made in the strategies for AIS management such as neuroprotective treatment, intravenous thrombolysis, and anticoagulation treatment, while AIS patients still suffer from elevating recurrence and increasing mortality. 6 , 7 , 8 In view of that there still exists several challenges in the management of AIS, the identification of reliable biomarker to monitor disease risk, severity, and prognosis is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…In China, stroke is the third highest cause of death with mortality of approximately 1.5 million in 2018, 3 which AIS may result in permanent disability, both functionally and cognitively; meanwhile, the morbidity of AIS is continuous increasing, which causes a huge economical and humanistic burden 4,5 . Over the decades, great advances have made in the strategies for AIS management such as neuroprotective treatment, intravenous thrombolysis, and anticoagulation treatment, while AIS patients still suffer from elevating recurrence and increasing mortality 6–8 . In view of that there still exists several challenges in the management of AIS, the identification of reliable biomarker to monitor disease risk, severity, and prognosis is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the low recognition of early AIS by the public in China, the ineffective pre-hospital treatment by medical and nursing staff, and the delay in in-hospital emergency care, only about 21.5% of patients arrive at the emergency department within 3 h of onset, and the average time from admission to thrombolytic drug treatment is 116 min, of which only about 9% of patients complete thrombolytic treatment within 1 h after admission, much lower than 50% in the United States. And it has been reported that after thrombolysis, 6 % of patients are still at risk of symptomatic intracranial hemorrhage, and 70% of patients still have symptoms of varying degrees of disability ( 8 , 9 ). The treatment situation of AIS patients in my country is very severe, and the treatment efficiency is not optimistic.…”
Section: Introductionmentioning
confidence: 99%